Analisi Strategi Digital Marketing Pada Produk Fashion Buttonscarves - Erwin Permana; Asmaa Nur izzati; Azizah, Evrila Nur (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2024)
As the digital ecosystem becomes more established, the business world has greater opportunities to reach wider markets. One of the popular business trends in digital media is the local fashion brand Buttonscarves. This research aims to analyze the digital marketing strategy for Buttonscarves products. The research was conducted using a qualitative approach. Data comes from search results and observations in various digital databases and official publications. The results of the analysis of digital marketing strategies for fashion buttonscarves products show that the use of technology as part of digital marketing has proven successful in expanding the market. In increasing online product marketing, Buttonscarves utilizes digital platforms and carries out several strategies. This strategy is to create an official website that is structured so that it can make things easier for potential consumers, make good use of social media by paying attention to aesthetics, collaborate with influencers and celebrities, collaborate with well-known Indonesian designers, collaborate with International Key Opinion Leaders (KOL), and carry out Collaboration with existing e-commerce such as Shopee, Tokopedia, Blibli and Zalora.